DO DIVIDEND SHOCKS AFFECT EXCESS RETURNS: AN EXPERIMENTAL STUDY - Draganac, Dragana (Economic Annals, 2017)
The dividend announcement of a company is an informational event that can cause underreaction, momentum, overreaction, post-dividend announcement drift, and mean reversion. It is the uncertainty surrounding dividend announcements that leads to such behavioural phenomena. Most authors consider that underreaction occurs after dividend shocks because new information about the dividend is being slowly and gradually built into the stock price. The effect of dividend shocks is often reflected in excess returns, which can last up to one year after the shock. The experiment described in this paper tests whether statistically significant excess returns are realized after a shock dividend announcement. Participants trade with the stocks of two companies, which only differ by dividend-generating stochastic process. The dividend process of Company 2 is a Merton-style jump-diffusion process (consisting of two parts: Brownian motion and Poisson jump), while the dividend process of Company 1 contains only the Brownian motion component. Statistically significant excess returns are expected when trading with Company 2 stocks. An autoregressive model is applied in order to test this hypothesis. The conclusion is that a dividend shock is followed by statistically significant excess returns in 20 of the 22 experiments, which implies that markets are inefficient after sudden and large changes in dividends. Underreaction and discount rate effects are identified.